KOMPARASI METODE DAKWAH DARUL ARQAM DAN DAKWAH MASJID NABAWI: RELEVANSI DALAM KONTEKS DAKWAH MODERN: Characteristics of the Da'wah of Darul Arqam, Characteristics of the Da'wah of the Prophet's Mosque, Comparison of the Da'wah of Darul Arqam and the Prophet's Mosque, Relevance in the Context of Modern Da'wah - Muhammad Ainudzaky Ainudzaky; Achmad Zuhdi Dh (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2025)
Islamic preaching has various strategies and methods that are adapted to the social, cultural and challenging contexts of the times. Two interesting approaches to study are the Darul Arqam da'wah applied in the early period of Islam in Makkah and the Prophet's Mosque da'wah which developed after the hijrah to Medina. This research discusses the characteristics of Darul Arqam's da'wah, the characteristics of the Prophet's Mosque's da'wah, and the comparison between the two and their relevance to da'wah today. This research uses a qualitative-descriptive method based on literature study with a historical approach. This research results in the conclusion that the Darul Arqam Da'wah focuses on exclusive coaching within a limited scope to build the faith and mental resilience of the people amidst the pressure of the Quraysh. Meanwhile, the preaching of the Prophet's Mosque is more open and inclusive, accommodating various social, educational, and governmental aspects in forming a harmonious Medina society. Both da'wah have relevance in modern da'wah, especially in the context of fostering Muslim communities amid the challenges of globalization.